Aquaporins in pancreatic ductal adenocarcinoma. Issue 12 (18th October 2021) - Bruun‐Sørensen, Anne Sofie; Edamana, Sarannya; Login, Frédéric H.; Borgquist, Signe; Nejsum, Lene N.
Abstract : Aquaporins are water channel proteins facilitating passive transport of water across cellular membranes. Aquaporins are over‐ or ectopically expressed in a multitude of cancers, including pancreatic ductal adenocarcinoma, which is a highly aggressive cancer with low survival rate. Evidence suggests that aquaporins can affect multiple cellular processes involved in cancer development and progression including epithelial‐mesenchymal transition, cellular migration, cell proliferation, invasion, and cellular adhesions. In pancreatic ductal adenocarcinoma, aquaporin‐1, aquaporin‐3, and aquaporin‐5 are overexpressed and have been associated with metastatic processes and poor survival. Thus, aquaporin expression has been suggested as diagnostic markers and therapeutic targets in pancreatic ductal adenocarcinoma.